2005
DOI: 10.2355/isijinternational.45.1014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen to Silicon Ratio on the Viscosity of Metallurgical Slags

Abstract: Viscosity is an important physical property, which influences the performance of slags, in metallurgical processes such as iron making, steelmaking and continuous casting. Viscosity of slags is strongly influenced by the chemical composition and the temperature. Experimental measurement of slag viscosity requires high temperature equipment and is time consuming. Empirical relations/calculations using certain chemical parameters have been attempted to predict the viscosity, which may then be used for controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…If IPT is taken as a measure of viscosity, O/Si ratio generally shows a slightly better correlation with the mould powder viscosities than the other two ratios. This agrees with the investigation by Santhy et al,9 who observed a steady correlation between O/Si ratio and viscosities for simple slag chemistries.In the work of Santhy et al,9 a growing need of a viscosity characterisation model for the iron-and steelmaking fluxes and slags was identified. In order to further understand the gap in mould flux characterisation, the authors progress one step further by developing the following relationships which can predict the IPT ribbon lengths from the mould flux chemistry based on O/Si ratio for both CaO and CaF 2 classes of mould fluxes…”
supporting
confidence: 93%
“…If IPT is taken as a measure of viscosity, O/Si ratio generally shows a slightly better correlation with the mould powder viscosities than the other two ratios. This agrees with the investigation by Santhy et al,9 who observed a steady correlation between O/Si ratio and viscosities for simple slag chemistries.In the work of Santhy et al,9 a growing need of a viscosity characterisation model for the iron-and steelmaking fluxes and slags was identified. In order to further understand the gap in mould flux characterisation, the authors progress one step further by developing the following relationships which can predict the IPT ribbon lengths from the mould flux chemistry based on O/Si ratio for both CaO and CaF 2 classes of mould fluxes…”
supporting
confidence: 93%
“…The experimental data point corresponding to 0 min of sputtering associated with the top surface consisted of the highest O total /Si ratio of 3.74, which was theoretically logical, owing to the high abundance of silanol groups and associated hydrogen-bonded water molecules on the surface. [27][28][29] However, the concentration of BO was experimentally found to be the highest at this point in depth. This unexpected outcome was confirmed to be true for the second category of SLS glass that was investigated separately, represented in Figure S3.…”
Section: Si2p Curve-fittingsmentioning
confidence: 82%
“…It is graphically portrayed in Figure 6. A high O/Si ratio is generally indicative of a depolymerized silicate network 27 . The presence of NBOs associated with network modifiers and hydrous species (SiOH/H 2 O) in the subsurface network of SLS glass increases the atomic ratio of O total /Si from the otherwise known value of 2.0 for fused silica (SiO 2 ) consisting of all Q 4 entities (four BOs without any NBO per silica tetrahedron).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of thermodynamic data allows for the calculation of viscosity for wide composition range, the feature of the silicate melts are not directly considered in their models. Santhy et al (2005) analyzed the trends of viscosities of slags in terms of O/Si ratio. In all cases, irrespective of the system and the temperature, the viscosity was found to decrease steadily with increasing oxygen to silicon ratio.…”
Section: Network Structured Fluidsmentioning
confidence: 99%